Ellagic acid inhibits migration and invasion by prostate cancer cell lines - Pornsiri Pitchakarn (2018)
Polyphenolic compounds from pomegranate fruit extracts (PFEs) have been reported to possess antiproliferative, pro-apoptotic, anti-inflammatory and anti-invasion effects in prostate and o ther cancers. However, the mechanisms responsible for the inhibition of cancer invasion remain to be clarified. In the present study, we investigated anti-invasive effects of ellagic acid (EA) in androgen-independent human (PC-3) and rat (PLS10) prostate cancer cell lines in vitro. The results indicated that non-toxic concentrations of EA significantly inhibited the motility and invasion of cells examined in migration and invasion assays. The EA treatment slightly decreased secretion of matrix metalloproteinase (MMP)-2 but not MMP-9 from both cell lines. We further found that EA significantly reduced proteolytic activity of collagenase/gelatinase secreted from the PLS-10 cell line. Collagenase IV activity was also concentration-dependently inhibited by EA. These results demonstrated that EA has an ability to inhibit invasive potential of prostate cancer cells through action on protease activity.